Could the rise in mortality rates since 2015 be explained by changes in the number of delayed discharges of NHS patients?. Issue 11 (2nd October 2017) - Green, Mark A; Dorling, Danny; Minton, Jonathan; Pickett, Kate E
Abstract : Background: 2015 saw the largest annual spike of mortality rates in England in almost 50 years. We examine whether these changes in mortality rates are associated with an indicator of poor functioning of health and social care: delay in hospital discharges. Methods: Office for National Statistics monthly data of death counts and mortality rates for the period August 2010–March 2016 were compared with delays in discharges from National Health Service (NHS) England data on transfers of care for acute and non-acute patients in England. Autoregressive Integrated Moving Average regression models were used in the analysis. Results: We estimate that each additional day an acute admission was late being discharged was associated with an increase in 0.394 deaths (95% CIs 0.220 to 0.569). For each additional acute patient delayed being discharged, we found an increase of 7.322 deaths (95% CIs 1.754 to 12.890). Findings for non-acute admissions were mixed. Conclusion: The increased prevalence of patients being delayed in discharge from hospital in 2015 was associated with increases in mortality, accounting for up to a fifth of mortality increases. Our study provides evidence that a lower quality of performance of the NHS and adult social care as a result of austerity may be having an adverse impact on population health.